Aplicar Guías De Aprendizaje En Biología Para Mejorar La Adquisición De Conocimiento En Las Estudiantes Del Grado 7 De La Institución Educativa San José Del Municipio De Circasia- Quindío (2015)
In this work, learning guides were applied in biology to seventh grade students of School San Jose in the municipality of Circasia - Quindío, which helped to stimulate favorable attitudes toward the appropriation of concepts in areas such as mitosis, meiosis, osmosis and diffusion. In this process the appropriation of concepts was evidenced by them, since they were carried out these methodologies: didactic lecture ¿, videos, pictures, experiments at home etc. Which ended with the implementation of the tutorials and the final evaluation, for comparison with initial results with those found at the end of the project? This may take ownership led to an easier way of concepts as such.